The interplay between managerialism and medical professionalism in hospital organisations from the doctors' perspective: a comparison of two distinctive medical units - Correia, T. (Health Sociology Review, 2013)
This in-depth qualitative research examines the interplay between medicine and management. It focuses on the reasons why doctors do not always implement administrative guidelines either uniformly or in their entirety, in a context that is expanding managerial supervision. More specifically, we investigated the extent to which managerialism is shaping doctors' perceptions of their role as doctors and their perceived position towards hospital management. We follow a sociological perspective and analyse structural, contextual and individual dimensions, going back to Weber's discussion of the meaning of action, in order to interpret how doctors act in two different medical units, one conventional and one cutting-edge. Our argument for analysing individual action in its specific context is that the differences within the medical profession give rise to distinct forms of professionalism and, with this approach, a more complex articulation between managerialism and professionalism can be brought to the debate on the health professions.